2021
DOI: 10.3389/fendo.2020.626322
|View full text |Cite
|
Sign up to set email alerts
|

Stem Cell Paracrine Signaling for Treatment of Premature Ovarian Insufficiency

Abstract: Premature ovarian insufficiency is a common disorder affecting young women and represents the worst-case ovarian scenario due to the substantial impact on the reproductive lifespan of these patients. Due to the complexity of this condition, which is not fully understood, non-effective treatments have yet been established for these patients. Different experimental approaches are being explored and strategies based on stem cells deserve special attention. The regenerative and immunomodulatory properties of stem … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 132 publications
0
15
0
Order By: Relevance
“…Importantly, for the first time, we found that CEFFE could repair the function of aged granulosa cells. Our previous studies have shown that CEFFE is rich in various growth factors, such as PDGF, BDNF, GDNF, and TGFβ, which are also abundant in the follicular fluid, contributing to the regulation of intrafollicular microenvironment and the maturation of granulosa cells and follicles ( 15 ). In contrast, PDGF and GDNF contents in the follicular fluid of patients with ovarian dysfunction (such as DOR and aging) were lower than those in young people with normal ovarian functions ( 42 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly, for the first time, we found that CEFFE could repair the function of aged granulosa cells. Our previous studies have shown that CEFFE is rich in various growth factors, such as PDGF, BDNF, GDNF, and TGFβ, which are also abundant in the follicular fluid, contributing to the regulation of intrafollicular microenvironment and the maturation of granulosa cells and follicles ( 15 ). In contrast, PDGF and GDNF contents in the follicular fluid of patients with ovarian dysfunction (such as DOR and aging) were lower than those in young people with normal ovarian functions ( 42 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, immune rejection and ethical risks of stem cell therapy and the limited source, low productivity, and difficulty in scaling up the production of exosomes have limited the clinical application of stem cells and exosomes ( 12 , 13 ). Several studies have shown that stem cells can contribute to tissue repair via secretion of growth factors ( 14 , 15 ). For example, adipose-derived stem cells can rescue the ovarian function via secretion of HGF and bFGF from stem cells ( 16 , 17 ).…”
Section: Introductionmentioning
confidence: 99%
“…But long-term HRT also has certain risks, such as the occurrence of endometrial cancer and breast cancer [1] . Mesenchymal stem cell transplantation is considered to be a very promising treatment strategy for reversing the negative effects of POI [4]. One of the key events that contribute to ovarian aging includes follicular atresia as it is associated with the pyroptosis and necrosis of granulosa cells and thecal cells in aging ovaries.…”
Section: Discussionmentioning
confidence: 99%
“…In the past ten years, mounting evidences have indicated the beneficial application of mesenchymal stem cells (MSCs) on the treatment of POF. Studies have noted that the transplanted MSCs exert their therapeutic effects mainly through the paracrine mechanism instead of direct cell replacement [ 2 ], and the MSCs can be used to treat POF mainly owing to its effects on OGC apoptosis [ 3 ]. However, there are certain limitations to the clinical application of MSCs, such as potential immunogenicity or tumorigenicity [ 4 ].…”
Section: Introductionmentioning
confidence: 99%